Kemelimpahan Penggerek Batang Padi (Lepidoptera : Pyralidae dan Noctuidae) di Sawah Organik dan Anorganik - Hadi, Mochamad (Universitas Negeri Semarang, 2020)
Rice stem borer is an insect pest (plant pests) that occurs throughout the year and is widespread in rice fields in Indonesia. The rice stem borer caterpillar (PBP) feeds on the growing point of the vegetative phase of the plant, causing symptoms of sundep. PBP caterpillars also eat the base of rice grains (generative phase), causing symptoms of outsides. PBP insects belong to the order Lepidoptera and the families Pyralidae and Noctuidae. Organic agriculture is considered to be more profitable than inorganic agriculture because the selling value of its products is higher, as well as because it does not use synthetic fertilizers and pesticides. Research on the abundance of PBP in organic rice fields using various methods is still not widely carried out. The research objective was to assess the abundance of PBP in organic and inorganic rice fields using various methods. The research was carried out on organic and inorganic rice fields with a rice-paddy-rice cropping pattern, by installing light traps, malaise traps diagonally and using a sweep net for adult PBP and making a square plot for adult PBP and eggs. The results showed that at the egg stage 2 PBP species were found, namely Scirpophaga incertulas (yellow PBP) and Sesamia inferens (pink PBP). Whereas in the adult stage, 4 PBP species were found, namely Schirpophaga incertulas, Schirpophaga innotata (white PBP), Sesamia inferens, Chilo auricilius (shiny PBP). In general, the most dominant and abundant type of PBP was yellow PBP, while other types of PBP were found in small numbers and occasionally. Penggerek batang padi adalah serangga OPT (organisme pengganggu tanaman) yang terdapat sepanjang tahun dan menyebar luas di persawahan di Indonesia. Ulat penggerek batang padi (PBP) memakan titik tumbuh tanaman fase vegetatif sehingga menimbulkan gejala sundep. Ulat PBP juga memakan pangkal bulir padi (fase generatif) sehingga menyebabkan gejala beluk. Serangga PBP termasuk dalam ordo Lepidoptera dan familia Pyralidae dan Noctuidae. Pertanian organik dinilai lebih menguntungkan dibanding pertanian anorganik karena nilai jual produknya lebih tinggi, juga karena tidak menggunakan pupuk dan pestisida sintetik. Penelitian kemelimpahan PBP di sawah organik dengan berbagai metode masih belum banyak dilakukan. Tujuan penelitian adalah mengkaji kemelimpahan PBP di sawah organik dan anorganik dengan menggunakan berbagai metode. Penelitian dilakukan pada sawah organik dan anorganik dengan pola tanam padi-padi-padi, dengan memasang light trap, Malaise trap secara diagonal dan menggunakan sweep net untuk PBP dewasa serta membuat plot kuadrat untuk PBP dewasa dan telur. Hasil penelitian menunjukkan bahwa pada stadia telur ditemukan 2 spesies PBP yaitu Scirpophaga incertulas (PBP kuning) dan Sesamia inferens (PBP merah jambu). Sedangkan pada stadia dewasa ditemukan 4 spesies PBP yaitu Schirpophaga incertulas, Schirpophaga innotata (PBP putih) , Sesamia inferens, Chilo auricilius (PBP berkilat). Secara umum jenis PBP yang paling dominan dan melimpah adalah PBP kuning, sedangkan jenis PBP yang lain, dijumpai dalam jumlah yang sedikit dan kadang-kadang